Protocolo de PCR para la detección de Brucella ovis, Histophilus somni y Actinobacillus seminis - Alvarez, Lucia Paula; Robles, Carlos Alejandro (EEA Bariloche, INTA, 2020)
Adaptado de Primers utilizados correspondientes al gen BOV_A0500 de B. ovis, tomados de: Tsolis, R.M., Seshadri, R., Santos, R.L., Sangari, F.J., Lobo, J.M., de Jong, M.F., Ren, Q., Myers, G., Brinkac, L.M., Nelson, W.C., Deboy, R.T., Angiuoli, S., Khouri, H., Dimitrov, G., Robinson, J.R., Mulligan, S., Walker, R.L., Elzer, P.E., Hassan, K.A., Paulsen, I.T., 2009. Genome degradation in Brucella ovis corresponds with narrowing of its host range and tissue tropism. PLoS One. 4, e5519.